Public-private partnerships in Europe: an update - Frédéric Blanc-Brude; Hugh Goldsmith; Timo Välilä (European Investment Bank (EIB), 2007)
This paper offers an updated description of the macroeconomic and sectoral significance of PPPs in Europe, without assessing PPPs from a normative perspective. It shows that, over the past fifteen years, more than one thousand PPP contracts have been signed in the EU, representing a capital value of almost 200 billion euro. While PPPs have in recent years become increasingly popular in a growing number of European countries, they are of macroeconomic and systemic significance only in the UK, Portugal, and Spain. In all other European countries, the importance of investment through PPPs remains small in comparison to traditional public procurement of investment projects. However, PPP procurement is used extensively for major projects and this is spreading out from transport into other sectors.
Keywords: H54; L33; L98; 330